The Role of Mass Media in The New Normal Era Pandemic Time COVID-19 in Banda Aceh City - Almukarramah Almukarramah; Ainal Fitri; Fitri Meliya Sari (Universitas Serambi Mekkah, 2022)
Communication and the masses have a strategic role in responding various problems that exist. In fact, communication and mass can be a form of early education that directly targets the wider community effectively and efficiently. The main discussion in this research is related to the important role of mass communication in the midst of the COVID-19 pandemic, as a form of prevention and early education to the public. The results of this study are, first, that communication and the masses have a central role in responding to the COVID-19 pandemic. Second, that the problems caused by the COVID-19 pandemic which has become a global problem have the potential to trigger a new social order or reconstruction, thus it is necessary to have close communication between stakeholders and the community in responding to this problem. Keywords: Communication, New Normal Era, COVID-19, Mass Media